2019
DOI: 10.1111/ppl.12966
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of somatic embryogenesis through proteomic approach and optimization of protocol in recalcitrant Musa spp.

Abstract: Somatic embryogenesis (SE) is a complex stress related process regulated by numerous biological factors. SE is mainly applicable to mass propagation and genetic improvement of plants through gene transfer technology and induced mutations. In banana, SE is highly genome dependent as the efficiency varies with cultivars. To understand the molecular mechanism of SE, a proteomics approach was carried out to identify proteins expressed during embryogenic calli (EC) induction, regeneration and germination of somatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 85 publications
1
20
0
Order By: Relevance
“…Pedroso and Pais reported that a high level of inorganic elements (Ca, K, Na, Mg, S, P and Fe) might be related to embryonic development or morphogenesis in Camellia japonica [71][72][73]. The calcium signaling pathway combined with stress and endogenous hormone-related proteins plays an important role in somatic embryo induction and germination, and the addition of CaCl 2 can promote callus induction and somatic embryo germination in banana [74]. Our results showed that the absence of one of the four groups of elements had a negative effect on SE and that macroelements were the most important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pedroso and Pais reported that a high level of inorganic elements (Ca, K, Na, Mg, S, P and Fe) might be related to embryonic development or morphogenesis in Camellia japonica [71][72][73]. The calcium signaling pathway combined with stress and endogenous hormone-related proteins plays an important role in somatic embryo induction and germination, and the addition of CaCl 2 can promote callus induction and somatic embryo germination in banana [74]. Our results showed that the absence of one of the four groups of elements had a negative effect on SE and that macroelements were the most important.…”
Section: Discussionmentioning
confidence: 99%
“…Plant regeneration via SE is highly genotype dependent [74,77]. Moreover, the growth state of each explant is divergent, thus, the phenotype can be different under the same external environment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that CaCl 2 (calcium chloride) can promote the induction of embryogenic calli (EC) and the germination of somatic embryos. Addition of 10 mM CaCl 2 increased the germination rate of somatic embryos by 51.79% [ 49 ]. The results of the present study indicate that an increase in the content of CaCl 2 from 0.44 g/L to 1.32 g/L can improve the germination coefficient of somatic embryos.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the proteomic changes associated with SE in banana, Marimuthu et al () chose to work on cv. Rasthali, a popular Asian cultivar.…”
mentioning
confidence: 99%
“…In the absence of any effective chemical control for this fungal infection, preserving the germplasm of popular banana cultivars and genetic modifications to generate disease‐resistant plants (Dale et al ) are the strategies that can save the banana from extinction. Efficient regeneration and SE will be extremely crucial in this effort, and the study by Marimuthu et al () will be a valuable resource for researchers working toward saving the banana.…”
mentioning
confidence: 99%